A qualitative study on behavioral and social drivers of COVID-19 vaccine amongst refugees and migrants in Pakistan. - Zahra Ali Padhani; Maryam Hameed Khan; Rahima Yasin; Abdu R Rahman; Sohail Lakhani; Mushtaq Mirani; Muhammad Khan Jamali; Zahid Ali Khan; Sana Khatoon; Riya Partab; Atta Ul Haq; Vinay Kampalath; et al. (PLOS Global Public Health)
Migrants and refugees are among the most disadvantaged populations, with limited evidence on the access and uptake of COVID-19 vaccination among them. Therefore this qualitative study explores the behavioral and social drivers of the COVID-19 vaccine among the refugee and migrant population in Pakistan through in-depth interviews and focus group discussions with regular and irregular migrants and refugees residing in Pakistan. Key informant interviews were conducted with stakeholders responsible for overlooking the COVID-19 vaccination process. A total of 18 participants were interviewed to gather insights on COVID-19 vaccine access, uptake, and behaviours among migrants and refugees. Data was collection from June to July 2022, in Karachi, Hyderabad, and Quetta. All the interviews were audio recorded, transcribed, translated, and thematically analysed on Nvivo software. The study found that refugee and migrant communities in Pakistan faced significant challenges to COVID-19 vaccination uptake, with barriers including misconceptions about vaccine safety and efficacy, fears of side effects, and mistrust spread by religious leaders. Participants were refused vaccinations at many centers despite government directives allowing vaccines for those without Computerized National Identity Cards (CNIC). Limited outreach and awareness efforts from the government, fears of identification and deportation, long wait times at vaccination centers, and the absence of female vaccinators in communities with strict gender norms further hindered access. Many participants also reported being charged for vaccination leading to lower vaccine coverage. Despite these challenges, some individuals were motivated to vaccinate due to workplace requirements, peer influence, or personal health concerns. Facilitators included door-to-door vaccination campaigns and school vaccination mandates. Vaccination camps set up by NGOs and government agencies at border areas and migrant-rich districts facilitated access. The study suggests targeted strategies to improve vaccination coverage, including provision of identification documents to migrants, inclusion in policy, and enforcement of multilingual communication to improve healthcare access.